2019
DOI: 10.1177/0748233719879312
|View full text |Cite
|
Sign up to set email alerts
|

Combination of fluoride and endosulfan induced teratogenicity and developmental toxicity in Swiss albino mice exposed during organogenesis

Abstract: The present investigation was conducted to evaluate the teratogenic and developmental toxicity of fluoride and endosulfan alone and in combination in pregnant Swiss albino mice exposed during the organogenetic period (5–14 days) of gestation. Fluoride (25.1 mg/kg body weight in water) and endosulfan (1.8 mg/kg bw by oral intubation) when administered alone and in combination (fluoride 25.1 mg/kg bw + endosulfan 1.8 mg/kg bw) to pregnant mice caused significant teratogenic effects in developing fetuses. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…There were no maternal deaths with fluoride (25.1 mg kg −1 bw) and endosulfan (1.8 mg kg −1 bw) given individually or in combination. A significant reduction in bw of animals treated with fluoride (25.1 mg kg −1 bw) and endosulfan (1.8 mg kg −1 bw) alone was observed, which is similar to the results of earlier reports (Collins et al, 2001; Gupta et al, 1978; Hiyasat et al, 2000; Sharma et al, 2019). Similar to our previous study (Sharma et al, 2019), maximum decrease was observed when doses of both fluoride and endosulfan were given together, indicating an additive effect.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…There were no maternal deaths with fluoride (25.1 mg kg −1 bw) and endosulfan (1.8 mg kg −1 bw) given individually or in combination. A significant reduction in bw of animals treated with fluoride (25.1 mg kg −1 bw) and endosulfan (1.8 mg kg −1 bw) alone was observed, which is similar to the results of earlier reports (Collins et al, 2001; Gupta et al, 1978; Hiyasat et al, 2000; Sharma et al, 2019). Similar to our previous study (Sharma et al, 2019), maximum decrease was observed when doses of both fluoride and endosulfan were given together, indicating an additive effect.…”
Section: Discussionsupporting
confidence: 91%
“…A significant reduction in bw of animals treated with fluoride (25.1 mg kg −1 bw) and endosulfan (1.8 mg kg −1 bw) alone was observed, which is similar to the results of earlier reports (Collins et al, 2001; Gupta et al, 1978; Hiyasat et al, 2000; Sharma et al, 2019). Similar to our previous study (Sharma et al, 2019), maximum decrease was observed when doses of both fluoride and endosulfan were given together, indicating an additive effect. The reduction in bw might be attributed to the toxicity caused by fluoride and endosulfan treatment as supported by increased degradation of lipids and proteins or probably due to the effect of these compounds on the gastrointestinal tract, resulting in decreased appetite (Goel et al, 2005; Mansour and Mossa, 2011; Venkatesanwarlu et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations